(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Children’s books for the present study were selected based on a set of specific criteria considering the large corpus of children’s literature available in India. The classification of the children’s books was done based on two guidelines — that is children’s books based on the genre (Picture books, chapter books—traditional and contemporary— and Young Adult fiction) and those of based on the age of the reader. The literary texts, including all genres of children’s literature read by all age categories, were selected on the criteria of women’s representation in them for the present research.People’s fantasies can follow the causes of kids’ dream fiction. Regardless of the way that they are viewed as the most conventional type of youngsters’ writing, they were, at the outset, diversion for grown-ups rather than babies’ accounts. People stories were told at all degrees of society and the Renaissance they likely began in labourers’ bungalows. Society stories have frequently been viewed as all-inclusive, truth be told, they vary when we move to start with one social or etymological zone then onto the next. As right on time as the Middle Ages kids were recognised from grown-ups, even though the medieval idea of adolescence contrasted from its cutting edge structure. Youngsters were not, for example, consequently dealt with by their folks, since another person, maybe an inaccessible family member, an employed babysitter or only a bystander, could carry out the responsibility also. The play was, in any case, expected to be ideal for the newborn child’s turn of events and a few researchers even suggested perusing instructive stories and singing tunes to youngsters. Indeed, even the possibility of an honest kid, commonly associated with Romanticism, has its underlying foundations in medieval times.